1992
DOI: 10.2307/3283709
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Onchocerca volvulus in Nodules Implanted in Immunodeficient Rodents

Abstract: Onchocerca volvulus is an obligate human parasite, and its study has been difficult due to an inability to maintain it outside the human host. We report the successful transplantation of onchocercomata containing living adult O. volvulus worms into immunodeficient C.B.-17.scid/scid (scid) mice or athymic rnu/rnu (nude) rats. Living, motile worms containing viable microfilariae were present in onchocercomata recovered from scid mice or nude rats for up to 20 wk, establishing a novel animal model for future inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Rajan et al previously described that exposed 'loops' of O. volvulus female worms embedded in onchocercomata could remain viable and contain developing mf for up to 20 wks post-implant in SCID mice [20], demonstrating the longterm feasibility of this approach. We speculate that the reduced biomass and less dense extra-cellular matrix of ochengi vs. volvulus onchocercomata may facilitate an increase in perfusion of host solutes, as well as our observations of neovascularization, to support protracted survival of implanted female macrofilariae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajan et al previously described that exposed 'loops' of O. volvulus female worms embedded in onchocercomata could remain viable and contain developing mf for up to 20 wks post-implant in SCID mice [20], demonstrating the longterm feasibility of this approach. We speculate that the reduced biomass and less dense extra-cellular matrix of ochengi vs. volvulus onchocercomata may facilitate an increase in perfusion of host solutes, as well as our observations of neovascularization, to support protracted survival of implanted female macrofilariae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to utilize inbred mouse strains, including lymphopenic strains, to establish Onchocerca macrofilarial infections from infectious stage (L3) larval inoculations, has thus far proven unsuccessful [19]. However, Rajan and colleagues demonstrated that O. volvulus female worm 'loops' , exposed from surrounding nodular encasement in excised nodules, could remain viable following implantation into Severe-Combined ImmunoDeficiency (SCID) mice [20].…”
Section: Introductionmentioning
confidence: 99%
“…volvulus adult worms survived in scid mice for up to 20 weeks while still containing motile mf, indicating that adult worms have no nutritional requirements unique to a human host [47]. It was concluded that this protocol required scid mice because they are unable to reject the cotransplanted human tissue.…”
Section: Implantation Of Adult Worms Into Scid Micementioning
confidence: 99%
“…In the case of O. volvulus, worms were transplanted s.c. into C.B-17 scid mice without prior isolation from surrounding human host tissue, i.e. still located in the onchocercoma excised from patients 24 h earlier [47]. Furthermore, O. gutturosa adult worms were transplanted into CBA or Shasha mice with and without surrounding connective tissue capsules of their bovine hosts [48].…”
Section: Immune Responses To Adult Wormsmentioning
confidence: 99%
“…O. volvulus will grow only in the natural human host and a select group of nonhuman primates (1). Recently, in an attempt to establish infection in a murine system, human onchocercomata (skin nodules containing adult worms) were subcutaneously implanted into SCID mice (70). After up to 20 weeks in the mouse, onchocercomata contained both viable adult worms and microfilaria.…”
Section: Filariasismentioning
confidence: 99%